Pendekatan Berdeferensiasi Proses dalam Pembelajaran IPS Sekolah Dasar - Herawati Aisyah; Nasution Nasution; Utari Dewi (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Learning, including the curriculum and approaches implemented, must continue to be adapted to student needs. Teachers need to know that each child has their own characteristics and learning styles, so that teachers can determine the right approach for their learning process. The appropriate approach in the independent learning perspective that is currently being implemented in the national education system is a differentiated learning approach that allows students to take a more active role in the learning process and the freedom to use their own learning styles to acquire skills and knowledge. This approach is appropriate if applied to social studies learning, social studies learning is a subject related to humans and the environment. The method used in this research is a literature study obtained by searching for literature sources that are relevant to the research topic. Through this differentiated learning, students can focus on their potential and skills and teachers can facilitate students by adjusting students' learning needs so that students can maximize their potential and skills.